The urgent need for randomized controlled trials in pregnant women with antiphospholipid antibodies—protecting women through research - Adams, Christine Graversgaard; Rudnicki, Jullie; Petersen, Berit Fabricius; Jacobsen, Søren; Schreiber, Karen (Frontiers in Lupus, 2026)
IntroductionObstetric antiphospholipid syndrome (OAPS) is an autoimmune disorder associated with pregnancy morbidity, including recurrent pregnancy loss, preeclampsia and fetal growth restriction. Despite standard of care (SoC) with low-dose aspirin (LDA) and low-molecular-weight heparin (LMWH), 20%–30% of pregnancies still result in adverse outcomes. The 2023 ACR/EULAR classification criteria have improved research standardisation, yet robust clinical evidence, including randomised controlled trials (RCTs), remains limited and current management largely relies on empirical practice and RCTs performed nearly two decades ago.MethodsIn this mini-review, with a particular focus on refractory OAPS, we summarise the quality of evidence and methodological limitations underpinning current therapeutic strategies. This included existing SoC and potential adjuvant treatments, such as hydroxychloroquine (HCQ), corticosteroids, statins, intravenous immunoglobulin (IVIG) and biologics.ResultsLDA and LMWH remain the cornerstone of OAPS care. Observational data suggest that HCQ may enhance live birth rates in refractory cases, while glucocorticoids offer limited benefit and pose maternal risks. Evidence for IVIG, statins, and biologics is sparse and primarily derived from small uncontrolled studies. With the exception of a few trials reported almost two decades ago, no RCTs have been conducted specifically in OAPS.DiscussionImproved management of OAPS requires higher-quality evidence. Trials in other high-risk pregnancy populations demonstrate that RCTs are feasible. Progress will depend on standardised pregnancy outcome measures, international collaboration with coordinated leadership and increased societal and regulatory recognition of the urgent need for research and funding.This mini-review synthesizes current knowledge on the treatment of refractory OAPS, identifies critical research gaps, and outlines key strategic elements needed to advance evidence-based care for this high-risk population.